A conceptual approach to integrating healthcare services: an investigation of the Portuguese case. (2018) - Dias, Ana; Simões, Jorge; Santana, Silvina
The aging of the Portuguese population and the need to ensure the financial sustainability of National Health Service claim for urgent changes. The provision of care is still very fragmented; therefore, how to integrate care is crucial to optimise the use of resources and to improve outcomes, especially regarding value created for patients. In this paper, we identify determinants of care integration and discuss strategic and structural alternatives that encourage it. The research had two phases. First, we conducted a literature review and four initial exploratory interviews, to position the study and to ground the next steps. Then, the object of study was redefined by a more exhaustive literature review and 15 semi-structured interviews with key experts, to outline the central concepts and dimensions under study and to delimit the field of study with a view to build a conceptual model for the analysis and understanding of healthcare integration.